ALLAN POE AS A SHORT STORY WRITER (American Journal of Research in Humanities and Social Sciences, 2023)
The main purpose of this article is to give briefly information about actuality Edgar Allan Poe and his literary works. The Famous works from the classic Edgar Allan phase include The Edgar Allan novel took shape mostly in England from 1790 to 1830 and falls within the category of Romantic literature. It acts, however, as a reaction against the rigidity and formality of other forms of Romantic literature. The Edgar Allan is far from limited to this set time period, as it takes its roots from former terrorizing writing that dates back to the Middle Ages, and can still be found written today by writers. But during this time period, many of the highly regarded Edgar Allan novelists published their writing and much of the novel's form was defined.